Violations of Emergent Norms Regarding COVID-19 Mitigation and Social Hygiene: An Application of Agnew’s General Theory of Crime - Kabiri, Saeed (Crime & delinquency, 2025)
This study examines self-reported violations of emergent norms and regulations regarding COVID-19 mitigation and social hygiene practices among a sample of high school students randomly selected from public schools in Rasht, Iran. The study seeks to explain these COVID-19 ordinance violations through the application of Agnew’s general integrated theory of crime. Findings demonstrate that life domains, motivations, and constraints have a direct effect on COVID-19 misbehavior. Moreover, life domains have an indirect effect on COVID-19 misbehavior through both constraints and motivations. Finally, the relationship between motivations and COVID-19 misbehavior is moderated by the peers domain, whereas the relationship between constraints and COVID-19 misbehavior is moderated by the family domain and school domain.